1995
DOI: 10.1021/bi00046a035
|View full text |Cite
|
Sign up to set email alerts
|

A Thermal Broadening Analysis of Absorption Spectra of the D1/D2/Cytochrome b-559 Complex in Terms of Gaussian Decomposition Sub-bands

Abstract: Absorption spectra of the isolated D1/D2/cytochrome b-559 complex have been measured in the temperature range 80-300 K. All spectra were analyzed in terms of a linear combination of Gaussian bands and the thermal broadening data interpreted in terms of a model in which the spectrum of each pigment site is broadened by (a) a homogeneous component due to linear electron-phonon coupling to a low-frequency protein vibration and (b) an inhomogeneous component associated with stochastic fluctuations at each pigment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 28 publications
3
27
0
Order By: Relevance
“…Part of these red states have previously been ascribed to the multimer of P-680 . 4 K spectra with deep valleys have also been reported in Triton-derived preparations (van Kan et al, 1990;Chang et al, 1994a;Cattanea et al, 1995), so it is not a rule of thumb that Triton-derived preparations show increased inhomogeneous disorder in the red absorption bands. In fact, we have now isolated RC short preparations using a slightly different procedure that show the same degree of structure in the 4 K absorption spectrum as the RC DM-3 preparation.…”
Section: Purity Of Ps II Rc Preparationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Part of these red states have previously been ascribed to the multimer of P-680 . 4 K spectra with deep valleys have also been reported in Triton-derived preparations (van Kan et al, 1990;Chang et al, 1994a;Cattanea et al, 1995), so it is not a rule of thumb that Triton-derived preparations show increased inhomogeneous disorder in the red absorption bands. In fact, we have now isolated RC short preparations using a slightly different procedure that show the same degree of structure in the 4 K absorption spectrum as the RC DM-3 preparation.…”
Section: Purity Of Ps II Rc Preparationsmentioning
confidence: 96%
“…Nevertheless, analysis of the spectral window of 660-690 nm yielded consistent results of all three spectra with five spectral components ( Table 2). More components will result in even better fits [see, e.g., Cattanea et al (1995)] but appeared not necessary to extract the basic features. The most important difference between RC DM-3 and RC short is the slightly larger bandwidth of the components peaking near 683 and 679 nm; the other features are virtually the same.…”
Section: Gel Filtrationmentioning
confidence: 99%
“…The spectra were deconvoluted as linear combinations of symmetric Gaussians whose parameters (peak wavelength, full-width at half-maximum, and percentage amplitude to the 630 -720-nm spectrum integral) were kept free. The only constraint considered was the final control of the total bandwidth in the 9 -11-nm range, as expected from the analysis of electron-phonon coupling and site-inhomogeneous broadening in a variety of antenna chlorophyll proteins (10,12,37,38) in the accepted solutions. For the sake of model simplicity and reducing the arbitrariness of the fitting, the minimal choice of adjustable parameters was always used, i.e.…”
Section: Fig 2 Isolation Of Reconstituted Cp24 Complexmentioning
confidence: 99%
“…Analysis of the Reaction Center trapping efficiency as a function of the different Chl spectral pools, present in the Photosystem II antenna, revealed that a 683-684 spectral form was most strongly coupled to the Reaction Center (Jennings et al 1991b. This spectral pool was subsequently shown to be also an important component of the Reaction Center complex (Cattaneo et al 1995) and compartment modeling of Photosystem II in terms of its component chlorophyll/protein complexes shows that this determines its strong coupling to Photosystem II primary photochemistry .…”
Section: Chemiosmotic Circuits In Bacterial Chromatophoresmentioning
confidence: 99%